Pengaruh Tanggung Jawab Profesi, Independensi, Integritas, Objektivitas, Dan Kompetensi Terhadap Etika Auditor - Charoline Cheisviyanny; Lili Anita (Wahana Riset Akuntansi, 2013)
The research aims to know the effect of professional responsibility, independency, integrity, objectivity, and competency to auditor’s ethic. The population of the research was the auditors in Public Accountant Office in Padang. The sample was chosen by total sampling method. The data was collected by questioners and analyzed by double regression analysis. The result show: 1) Professional responsibility positive significantly effect to auditor’s ethic. 2) Independency does not positive significantly effect to auditor’s ethic. 3) Integrity does not positive significantly effect to auditor’s ethic. 4) Objectivity positive significantly effect to auditor’s ethic. 5) Competency does not positive significantly effect to auditor’s ethic. Keywords: auditor’s ethic, proffesional responsibility, independency, integrity, objectivity, competency